The effect of static mixer on the properties and performance of aerobic granules under different organic loading rates in treating synthetic textile wastewater - Suryati, Sulaiman; Abdul Syukor, Abd Razak; Azmi, A.; Khalida, M. (IOP Publishing Ltd., 2021)
Biogranulation is considered a promising technology in biological wastewater treatment due to its high effluent treatment quality, strong ability to withstand organic loading, strong microbial structure and high capability to remove organics, nitrogen and phosphate. Organic loading rate (OLR) is known as one of the significant factors in biogranulation process. Aerobic granules can be developed under different OLR conditions. Microorganisms are starved at low OLR while microbial growth accelerates at high OLR. The main objective of this study was to investigate the effect of various OLRs on the physical characteristics and treatment performance of aerobic granules in treating synthetic textile wastewater. Two reactors named as R4Y and R4N were used, where R4Y was a reactor with static mixer and R4N was without the static mixer. The OLR of 2.0, 2.5 and 3.0 kg/m3.day were examined during the post development study. The study demonstrated that OLR affected the performance of biogranules. The physical characteristics of biogranules and removal efficiencies of the reactor with static mixer seemed to be better as compared to the reactor without static mixer with increasing of OLR. The granules of R4Y had better physical strength with IC of 19.6% and more excellent settling ability with SV of 82.7 m/h and SVI of 24.6 mL/g. The findings proved that static mixer had a positive influence in biogranulation system and therefore, will lower the energy consumption and operational cost.